Dietary strategies to recover from exercise-induced muscle damage. (March 2014) - Sousa, Mónica; Teixeira, Vítor H.; Soares, José
Abstract Exhaustive or unaccustomed intense exercise can cause exercise-induced muscle damage (EIMD) and its undesirable consequences may decrease the ability to exercise and to adhere to a training programme. This review briefly summarises the muscle damage process, focusing predominantly on oxidative stress and inflammation as contributing factors, and describes how nutrition may be positively used to recover from EIMD. The combined intake of carbohydrates and proteins and the use of antioxidants and/or anti-inflammatory nutrients within physiological ranges are interventions that may assist the recovery process. Although the works studying food instead of nutritional supplements are very scarce, their results seem to indicate that food might be a favourable option as a recovery strategy. To date, the only tested foods were milk, cherries, blueberries and pomegranate with promising results. Other potential solutions are foods rich in protein, carbohydrates, antioxidants and/or anti-inflammatory nutrients.